2011
DOI: 10.1002/pits.20562
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the middle school environment: The context for student behavior beyond the classroom

Abstract: This article describes the use of an observation system to measure middle school staff practices, environment characteristics, and student behavior in the school common areas. Data were collected at baseline from 18 middle schools participating in a randomized controlled trial of school‐wide Positive Behavior Support. The observations were reliable and showed sensitivity to differences between school settings and between schools. Multilevel models with students nested in schools were used to examine the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 42 publications
(39 reference statements)
3
44
0
1
Order By: Relevance
“…Assessing School Settings: Interactions of Students and Teachers (ASSIST; Rusby, Crowley, Sprague, & Biglan, 2011;Rusby, Taylor, & Milchak, 2001). The ASSIST observational measure evaluates social processes occurring in the classroom.…”
Section: Methodsmentioning
confidence: 99%
“…Assessing School Settings: Interactions of Students and Teachers (ASSIST; Rusby, Crowley, Sprague, & Biglan, 2011;Rusby, Taylor, & Milchak, 2001). The ASSIST observational measure evaluates social processes occurring in the classroom.…”
Section: Methodsmentioning
confidence: 99%
“…The data was gathered through questionnaire, in-depth interview and field observation, primarly used checklist for data confirmation (Jamal et al, 2013;Rusby, Crowley, Sprague, & Biglan, 2011). The questionnaire was developed from Adiwiyata school assessment criteria (Ministry of Environment's Regulation number 5, 2013).…”
Section: School Of 3 Sungai Tebelianmentioning
confidence: 99%
“…Middle school students are at a pivotal stage in development in which they begin to experience emotional, social, physical, and cognitive changes that have long-term effects (Biglan, Crowley, Rusby, & Sprague, 2011). Emotional states often become less positive and less stable due to mood disruptions, risk behavior, and conflict with parents (Arnett, 1999;Biglan et al, 2004).…”
Section: Behavior Of Middle School Studentsmentioning
confidence: 99%
“…By reducing social problems and increasing academic achievement in a school setting, schools can work toward creating a more positive school climate that fosters successful learning and cognitive development. Biglan et al (2011) conducted a study in which they observed the behavior of middle schools students and staff, evaluating schools that tried to integrate PBIS strategies and behaviors. The study defined problematic behavior of students as being noncompliant, exhibiting potential dangerous action, and physical and/or verbal aggression toward peers (Biglan et al, 2011).…”
Section: Pbismentioning
confidence: 99%
See 1 more Smart Citation